Venetoclax plus cyclophosphamide and cytarabine as induction regimen for adult acute myeloid leukemia - Zhang, Baohang; Liu, Qingguo; Li, Junfan; Hu, Yimin; Zhao, Xin; Huang, Pingping; Li, Shangzhu; Wang, Ying (Frontiers in Oncology, 2023)
Background The efficacy of induction chemotherapy (IC) for acute myeloid leukemia (AML) has improved significantly with the application of targeting drugs. Our previous study showed that a 4-day IC regimen of cyclophosphamide (CTX) and Ara-C [CA (4 + 3)] achieved similar complete remission (CR) rate (80%) compared with the traditional 7-day regimen, and the survival rate appeared to be better. Methods In this pilot study, we further shortened the CA regimen to 3 days, added low-dose venetoclax (VEN, 200 mg/day) (VCA), and reported the efficacy and safety here. Results Twenty-five newly diagnosed adult AML patients were enrolled in this study and evaluated for the remission rate after one cycle of the VCA regimen. The CR/Cri was 92%, and all these patients had undetectable minimal residual disease (MRD−). The estimated overall survival at 12 months was 79.3%. The median time for both platelet recovery and absolute neutrophil count recovery was 16 days, faster than that of traditional IC. Compared with the previous CA (4 + 3) regimen, a higher CR rate (92% vs. 80%, P < 0.01) and a deeper degree of remission (CRMRD− rate, 92% vs. 45%, P < 0.01) were found in the VCA group. Conclusions This study showed that the 3-day CTX and Ara-C regimen is highly effective in newly diagnosed AML patients, and the addition of VEN to the CA regimen achieves higher and deeper one-course remission.